The Hardware Trojan War Attacks, Myths, and Defenses - Bhunia, Swarup; Tehranipoor, Mark M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book, for the first time, provides comprehensive coverage on malicious modification of electronic hardware, also known as, hardware Trojan attacks, highlighting the evolution of the threat, different attack modalities, the challenges, and diverse array of defense approaches. It debunks the myths associated with hardware Trojan attacks and presents practical attack space in the scope of current business models and practices. It covers the threat of hardware Trojan attacks for all attack surfaces; presents attack models, types and scenarios; discusses trust metrics; presents different forms of protection approaches - both proactive and reactive; provides insight on current industrial practices; and finally, describes emerging attack modes, defenses and future research pathways.
Part I. Hardware Trojan Preliminaries -- Chapter 1.Introduction -- Chapter 2.Introduction to Hardware Trojans -- Part II. Hardware Trojan attacks: Threat Analysis -- Chapter 3.Hardware Trojan Attacks in SoC and NoC -- Chapter 4. Hardware IP Trust -- Chapter 5. Hardware Trojans in Analog, Mixed-Signal and RF ICs -- Chapter 6. Hardware Trojans and Piracy of PCBs -- Part III. Detection-Logic Testing -- Chapter 7. Logic Testing for Hardware Trojan Detection -- Chapter 8. Formal Approaches to Hardware Trust Verification -- Chapter 9. Golden-free Trojan Detection -- Part IV-Detection-Side Channel analysis -- Chapter 10. Detecting Hardware Trojans using Delay Analysis -- Chapter 11. Reverse-Engineering Based Hardware Trojan Detection -- Part VI. Emerging Trent, Inductrial Practices, New Attacks -- Chapter 15. Hardware Trust in Industrial SoC Designs: Practice and Challenges -- Chapter 16.Conclusion and Future Work.
Keywords: Electronic circuits; Data protection; Cryptography; Data encryption (Computer science).; Electronics; Computers; Electronic Circuits and Systems; Data and Information Security; Cryptology; Electronics and Microelectronics, Instrumentation; Hardware Performance and Reliability